Knowledge about bronchial asthma management in primary health care physicians in Al-Khobar City, Saudi Arabia - Haneen A Yousef; Manal Koura; Abdullah A Yousef (Wolters Kluwer Medknow Publications, 2015)
Context: The prevalence of bronchial asthma (BA) is increasing in the Kingdom of Saudi Arabia. Primary health care (PHC) centers follow the national protocol, which is based on the severity of the disease for the management of asthma. The Saudi initiative for asthma (SINA) management adopted from the global initiative for asthma guidelines, which was recommended by several recent studies, is based on the control level of asthma. Aims: To assess the knowledge of PHC physicians and family medicine (FM) residents in Al-Khobar, about the management of BA. Methodology: A cross-sectional study was conducted in all PHC centers and the university FM clinic in Al-Khobar. All PHC physicians and 3 rd and 4 th year FM residents were included in the study. A self-administered questionnaire developed according to SINA guidelines was used to assess theoretical knowledge of BA, and a predesigned checklist was used to assess the different inhaler techniques. Scoring was established and collected data were analyzed. Results: Only 8% of the sample had good theoretical knowledge of BA; 41% had poor knowledge. The knowledge of the residents was better than that of the PHC physicians. The mean knowledge score was significantly better among those using guidelines compared to the rest. About 23% had good knowledge of inhaler techniques. Knowledge of PHC physicians and FM residents about dry powder inhalers was deficient, and PHC physicians had little knowledge of metered dose inhalers with spacers. Conclusion: The knowledge of physicians about the management of BA was deficient. The national guidelines based on the level of control for asthma management should be updated and physicians given periodic training.